PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP KEMAMPUAN MENULIS TEKS ULASAN PADA SISWA KELAS 8 MTs SWASTA MIFTAHUL HUSNA TAHUN PEMBELAJARAN 2021/2022 - Nuraidah Nuraidah; Abdullah Hasibuan (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to determine the effect of the inquiry learning model on the writing skills of review text in class VIII students of MTs Miftahul Husna Private and to find out how the application of the inquiry learning model to writing skills of review text in class VIII students of MTs Miftahul Private. The type of research conducted in this study is a Quantitative Approach. The population in this study were all class VIII students at Miftahul Husna Private MTs as many as 120 students and the sample used in this study was 25% of the total population, namely 30 students. The data collection technique used in this study is to use test and observation methods. Data Analysis Techniques In this study the authors used validity and reliability tests. The results of the research in this study are the value of writing review text skills that are learned by applying the usual/conventional learning model, the average percentage of student scores is 41.56 <70% of the specified KKM, it can be concluded that